An International Expert Delphi Consensus on Defining Textbook Outcome in Liver Surgery (TOLS). Issue 5 (10th May 2023) - Görgec, Burak; Benedetti Cacciaguerra, Andrea; Pawlik, Timothy M.; Aldrighetti, Luca A.; Alseidi, Adnan A.; Cillo, Umberto; Kokudo, Norihiro; Geller, David A.; Wakabayashi, Go; Asbun, Horacio J.; Besselink, Marc G.; Cherqui, Daniel; et al.
Abstract : Objective: To reach global expert consensus on the definition of TOLS in minimally invasive and open liver resection among renowned international expert liver surgeons using a modified Delphi method. Background: Textbook outcome is a novel composite measure combining the most desirable postoperative outcomes into one single measure and representing the ideal postoperative course. Despite a recently developed international definition of Textbook Outcome in Liver Surgery (TOLS), a standardized and expert consensus-based definition is lacking. Methods: This international, consensus-based, qualitative study used a Delphi process to achieve consensus on the definition of TOLS. The survey comprised 6 surgical domains with a total of 26 questions on individual surgical outcome variables. The process included 4 rounds of online questionnaires. Consensus was achieved when a threshold of at least 80% agreement was reached. The results from the Delphi rounds were used to establish an international definition of TOLS. Results: In total, 44 expert liver surgeons from 22 countries and all 3 major international hepato-pancreato-biliary associations completed round 1. Forty-two (96%), 41 (98%), and 41 (98%) of the experts participated in round 2, 3, and 4, respectively. The TOLS definition derived from the consensus process included the absence of intraoperative grade ≥2 incidents, postoperative bile leakage grade B/C, postoperative liver failure grade B/C, 90-day major postoperative complications, 90-day readmission due to surgery-related major complications, 90-day/in-hospital mortality, and the presence of R0 resection margin. Conclusions: This is the first study providing an international expert consensus-based definition of TOLS for minimally invasive and open liver resections by the use of a formal Delphi consensus approach. TOLS may be useful in assessing patient-level hospital performance and carrying out international comparisons between centers with different clinical practices to further improve patient outcomes.